Modeling of Heat Transfer in Massive Concrete Foundations Using 3D-FDM - Dina M. Mansour; Ahmed M. Ebid (Salehan Institute of Higher Education, 2023)
Analyzing and modeling the thermal behavior of mass concrete elements has been widely investigated by several researchers. Lately, many contemporary finite element packages have embedded modules for analyzing thermal behavior. Unfortunately, these packages are quite complex and require experts to be properly implemented. This paper proposes a simple and practical approach using the 3D-Finite Difference Model (3D-FDM) developed by MS-Excel to overcome the complexity of the other FE models. The model is utilized to predict the thermal behavior of actual bridge pile caps (3D model) rather than the previously developed 2D models in earlier research. The results of the analysis are compared with the concrete temperatures that were experimentally obtained from the site. Site data was collected using 18 thermocouple probes (K type) that were installed in two pile caps. These thermocouples were installed before concrete pouring to monitor the temperatures generated due to the exothermic reaction of the cement, which occurs during casting and the maturity period of concrete. The readings were registered every 3 hours for 7 days after concrete placement. This research provides a comparison between the recorded site data and the thermal analysis based on the proposed 3D-FDM. Results proved that concrete temperature time histories at different locations of the bridge pile caps could be properly predicted using the developed 3D-FDM. Doi: 10.28991/CEJ-2023-09-10-05 Full Text: PDF